RANCANG BANGUN DATA LOGGER MONITORING VIBRASI PADA MOTOR LISTRIK 6,3 KV BERBASIS IOT SECARA REAL TIME DI PLTU JERANJANG - Satriya Guna Adnyana, Putu Agus; Sari Hartati, Rukmi; Dyana Arjana, I Gede (Jurnal SPEKTRUM; Vol 9 No 1 (2022): Jurnal SPEKTRUM, 2022)
As a power plant industry, PLTU Jeranjang OMU (Operation and Maintenance Unit) owned one of 6.3 kV nominal voltage induction motor that has critical characteristic that drives the water pump into the boiler room which always has to operate. This motor has been equipped with temperature sensor in real time that can monitor the temperature of bearing motor. However, manual control is still applied in vibration monitoring. It is done by taking the vibration data once a week, and there is no deviation data found in real time. The result of this study shows that the prototype of IoT-based vibration monitoring data logger that is designed using the blynk application obtained the average of sensor deviation of 2%. Alarm notification of each sensors deliver "warning" if the vibration value indicates ? 4,5-70 mm/s and alarm notification delivers "emergency" if the vibration value indicates ? 7,1 mm/s in concordance with the ISO 10816-3 vibration standard. Although, the performance of sensor data storage has successfully storing the data with 8 GB microSD card, then will be fully charged in 4629 days or 154 months and 3 days.